Knowledge On Life-style Related Non-communicable Disease (NCDs) Among Indigenous People (Orang Asli) In Negeri Sembilan, Malaysia - Muslimah Ithnin; Mohd Dzulkhairi Mohd Rani; Mohd Azmani Sahar; Nadia Mohd Effendy; Khadijah Hasanah Abang Abdullah; Muhammad Shamsir Mohd Aris; Norsham Juliana Nordin; Nadeeya'ayn Umaisara Mohamad Nor (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
INTERNATIONAL FAMILY HEALTH CONFERENCE 2019 (I-FaH 2019) Held at Oriental Crystal Hotel, Kajang, Selangor, Malaysia On 4-5th September, 2019 Malaysian Journal of Medicine and Health Sciences (Volume :15 Supp 4)